Analisis Validitas E-LKPD Fluida Statis berbasis Dual Space Inquiry Framework dalam Menstimulasi Keterampilan Proses Sains - Afriza, Nada; Novitra, Fuja; Mufit, Fatni; Anshari, Rio (TSAQOFAH, 2026)
The development of valid digital teaching materials is a key prerequisite for stimulating students’ science process skills in physics learning, particularly on static fluid topics for Phase F students at senior high schools/Islamic senior high schools (SMA/MA). This study aims to analyze the validity level of a Static Fluid E-Worksheet (E-LKPD) based on the Dual Space Inquiry Framework (DSIF) as a digital learning material designed to foster students’ science process skills. This Research and Development (R&D) study is limited to the validity phase and employs the ADDIE development model, encompassing the analysis, design, and development stages. Data were collected using expert validation sheets and analyzed with Aiken’s V formula. The validation process involved three expert validators in Physics Education who assessed six components: content feasibility, visual communication, instructional design, software utilization, DSIF stages, and indicators of science process skills. The analysis results show that all validity aspects obtained an average Aiken’s V value of 0.90, categorized as very valid. These findings indicate that the DSIF-based E-LKPD meets criteria of substantive accuracy, presentation quality, visual design, and pedagogical alignment, and is thus suitable for use as a digital teaching material in static fluid physics learning. The developed product has the potential to be used in inquiry-based learning and to support the enhancement of students’ science process skills; therefore, further studies are recommended to examine its practicality and effectiveness through direct implementation with students so that its impact and applicability in real learning contexts can be understood more comprehensively.